Caracterización fisicoquímica, microbiológica y organoléptica de un néctar elaborado a partir de mucílago de cacao (Theobroma cacao L.) de dos variedades (Nacional y CCN51) adicionando mango (Mangifera indica) - Merelo Palma, Julissa Fernanda (2025)
This study addresses the physical-chemical, microbiological and organoleptic characterization of a nectar made from cocoa mucilage (Theobroma cacao L.). Which were analyzed the physical-chemical properties (pH, Brix and titratable acidity), the microbiological load complying with the safety standards and the sensory characteristics such as (flavor, aroma and color). For this, a completely randomized block design (DCA) was carried out, which led to evaluate the 6 treatments varying the concentration of mucilage (50% - 70%) and a fixed concentration of mango pulp adjusting to the parameters allowed within the regulations (25%), with the participation of 30 tasters. In which the characteristics such as flavor, aroma, texture and color were analyzed to determine the acceptability of the best treatment. The research concluded by showing in the ANOVA analysis the level of significance of pH (p<0.0054, R²=0.81), °Brix (p<0.0031, R²=0.83) and acidity (p<0.0001, R²=1.00). The treatments complied with the established parameters, highlighting among them the T4 treatment with a pH 4.0 and 4.3 with reference to °Brix between 11 and 12 and titratable acidity between 0.72%, in accordance with the INEN: 2337:2008 regulations. Among it, the T4 treatment also corresponds in its composition 70% cocoa mucilage of the CCN51 variety and 25% mango pulp, which achieved an acceptability of 96% in contrast to the other treatments. The microbiological analysis determined the count of molds and yeasts at <10 CFU/mL, complying with INEN 1529-10 regulations.